MENINGKATKAN KEMAMPUAN MAHASISWA DALAM MENYIMAK BAHASA INGGRIS LISAN - Muhammad Rifqi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
It is believed that the studentsâ€™ habit of listening correlate with their listening proficiency. This study tried to investigate this view. The learnersâ€™ ability in listening to the spoken language is indicated by their ability to give response or comment to the spoken language that they have listened. The research was conducted in EFL class setting. Thirty five of the seventy nine students were taken as the subjects of the research. The research subjects were the fourth students of English Department Dian Nuswantoro University taking â€œListening Comprehension IVâ€. They were asked to answer the questionnaires to measure their habit.The studentâ€™s scores in â€œListening Comprehension IVâ€ weredocumented and used as their proficiency level. The two variables were then analyzed by using Pearson Product-Moment test. The output of the statistical analysis showed that the two variables have significant correlation indicated by 70.4% coefficient correlation and the level of significance was 0.0. The results of the statistical analysis indicate that the better the studentsâ€™ habit of listening the better their listening proficiency. Based on the findings, the teacher of English is recommended to shape the studentsâ€™ habit by giving much task in order to expose them toEnglish especially spoken English.Key words: Listening, Pearson Product-Moment test, Spoken English, Studentsâ€™ability,